Analisis Kebutuhan Pelanggan dengan Pendekatan Quality Function Deployment dalam Perancangan Sistem Pendukung Keputusan Kenaikan Jabatan Akademik Dosen - Kusmendar Kusmendar; Awang Hendrianto Pratomo; Agus Ristono (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
The development of information technology in the era of the industrial revolution 4.0 cannot be denied. The development demands an increase in the capability and competence of Human Resources. This study aims to build a decision support system for submitting a lecturer's academic functional position with Quality Function Deployment (QFD) so that the system is following the needs and desires of the lecturer regarding the submission of academic functional positions. The system is expected to be accessed independently by lecturers so that lecturers do not experience difficulties in calculating credit scores. The approach to managing system requirements with QFD will encourage and lead to the effectiveness of the voice of the customer (VoC) as the basis for customer satisfaction. VoC helps identify the gap between the interests and needs of customers. This shows the order of priority in designing a website for the management of functional positions for lecturers is the aspects of (1) information, (2) convenience, (3) appearance, (4) design, (5) service, and (6) security.